Strip meniscometry tube: a rapid method for assessing aqueous deficient dry eye. (4th July 2019) - Alshammeri, Saleh; Madden, Louise; Hagan, Suzanne; Pearce, E Ian
Abstract : Background: The aim of this study was to investigate the utility of strip meniscometry tube (SMTube) for the quantitative assessment of the tear film, by comparing it to measurements of tear turnover rate using the gold standard method, fluorophotometry. Also, to determine the viability of this test as a diagnostic tool for aqueous deficient dry eye (ADDE), to inform appropriate clinical management. Methods: Thirty‐two participants (15 ADDE; 17 non‐ADDE) were recruited. Tear turnover rate of the right eye of each subject was conducted with an automated scanning fluorophotometer and SMTube test was conducted. Tear meniscus height was assessed using a slitlamp biomicroscope and eyepiece graticule. Results: Significant differences between the ADDE and the non‐ADDE groups were found for all measures: tear turnover rate 7.9 ± 1.8 versus 19.6 ± 5.9 per cent/minute (p < 0.001), SMTube 3.2 ± 1.1 versus 5.7 ± 2.3 mm (p = 0.001) and tear meniscus height 0.18 ± 0.05 versus 0.23 ± 0.04 mm (p = 0.004). Moreover, significant correlations were found between tear turnover rate and SMTube (rho = 0.78, p < 0.001), tear turnover rate and tear meniscus height (rho = 0.54, p < 0.001) and SMTube and tear meniscus height (rho = 0.47, p < 0.01). Using a receiver operating characteristic curve, SMTube showed a sensitivity of 67 per cent and a specificity of 88 per cent for the diagnosis of ADDE. Conclusion: Given its performance, availability, speed and the fact it is relatively cheap, the study shows that the SMTube can be used as an alternative to fluorophotometry to assess tear production. It appears from the results that SMTube is a viable minimally invasive test for the diagnosis of ADDE.